Analysis of panel data - Hsiao, Cheng, 1943- (Econometric Society monographs, 2003)
This second edition is a substantial revision of the highly successful first edition of 1986. The thorough discussion of theory and the judicious use of empirical examples make this book useful to graduate students and advanced researchers in economics, business, sociology, political science, etc.